The Effect Of Social Media Marketing, Word Of Mouth, And Effectiveness Of Advertising On Brand Awareness And Purchase Intention On Grab Application Users Domicile Of Tangerang - Ezra Aileen; Orlando Gaberamos; Innocentius Bernarto; Lamhot Henry Pasaribu (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of social media marketing, word of mouth, and the effectiveness of advertising on brand awareness and purchase intention of Grab application users and to find out the partial relationship between the independent variable and the dependent variable. The sample in this study amounted to 100 respondents consisting of Grab application users domiciled in Tangerang who were selected using the convenience sampling technique. The data in this study were obtained using a questionnaire with a Likert scale. Based on the results of data analysis show that social media marketing and word of mouth. Do not have a positive effect on brand awareness, the effectiveness of advertising has a positive effect on brand awareness. In addition, social media marketing. Has a positive influence on purchase intention, while word of mouth does not have a positive influence on purchase intention. Effectiveness of advertising has a positive influence on purchase intention. Likewise, brand awareness has a positive influence on purchase intention..